1964
DOI: 10.1104/pp.39.6.1008
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Aspects of Parasitism in Mistletoes (Arceuthobium and Phoradendron). II. The Photosynthetic Capacity of Mistletoe

Abstract: In the preceding paper (7) it was noted that the true mistletoe, Phoradendron, derives very little if any carbohydrate from its host, while the dwarf mistletoe, Arceuithobiutm, draws heavily upon the photosynthate of its host. These findings imply that Phoradendron is capable of furnishing its own energy requirements but say little regarding the extent of dependence of Arceuthobium upon its host for carbohydrates.The aerial shoots of Arceuthobium frequently exhibit an off-green color which Peirce (9) claimed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
19
0
6

Year Published

1965
1965
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(27 citation statements)
references
References 11 publications
2
19
0
6
Order By: Relevance
“…Following the early work of Hull and Leonard (7,8), Ehleringer, Schulze and co-workers (5,18) have shed light on the principles underlying diversion of host resources to xylem-tapping mistletoes. A common feature is that mistletoe leaves have a Tn' in excess of that of their host, thus favoring the flux of resources to the parasite.…”
mentioning
confidence: 99%
“…Following the early work of Hull and Leonard (7,8), Ehleringer, Schulze and co-workers (5,18) have shed light on the principles underlying diversion of host resources to xylem-tapping mistletoes. A common feature is that mistletoe leaves have a Tn' in excess of that of their host, thus favoring the flux of resources to the parasite.…”
mentioning
confidence: 99%
“…Carbohydrate storage in the dwarf mistletoe endophytic system before thinning could reduce dependence of mistletoe on resources from the host tree supplied after thinning. Early studies suggested that carbohydrate acquired by dwarf mistletoes from host xylem sap accumulated primarily in the endophytic system (Rediske and Shea 1961;Hull and Leonard 1964b). However, more recent evidence from A. oxycedri indicated accumulation of most compounds, including carbohydrates, in the aerial shoots of dwarf mistletoe with little accumulation in the endophytic system (Rey et al 1991).…”
Section: Discussionmentioning
confidence: 96%
“…The dwarf mistletoes are similar to the leafy mistletoes of the Loranthaceae and other families because they acquire all of their water and nutrients from their hosts (Fisher 1983;Lamont 1983). However, dwarf mistletoes differ from many other types of mistletoe because they are essentially leafless and are more heterotrophic (Hull and Leonard 1964b;Miller and Tocher 1975;Logan et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Chlorophyll concentrations are low in some taxa like Arceuthobium and Tristerix aphyllus; in at least some leafy mistletoes, in contrast, the concentration of leaf chlorophyll appears to be roughly the same as that of the host (Hull and Leonard 1964b). The question of photosynthesis in mistletoes, however, must be seen in relation to the intake of water and nutrients from the host.…”
Section: Haustoria In Santalalesmentioning
confidence: 95%